Creating the transdisciplinary individual: Guiding principles rooted in studio pedagogy - Morales, Melita (Journal of Interdisciplinary Studies in Education, 2017)
It is widely recognized that the great challenges of the 21st Century cannot be understood or addressed through one discipline operating in a silo of research. Solutions to grand scale problems require varied expertise and multiple disciplinary methodologies to generate plausible solution strategies. The individuals involved in transdisciplinary research projects must be capable of employing scientific methods and traditional research skills, as well as engaging additional methods of inquiry such as those used in an art or design studio. In this paper, I first look at literature on transdisciplinarity and note the pattern of importance placed on the transdisciplinary individual. Secondly, I argue that studio pedagogy is integral to fostering the growth of the transdisciplinary individual capable of multi-modal inquiry practices.